Answer:
4 ( 8 - 2 ) = (-3) + 7 -> this is a false statement
Step-by-step explanation:
4 ( 8 - 2 ) = ( -3 ) + 7
Simplify the parenthesis
4 ( 6 ) = (-3) + 7
Multiply;
24 = (-3) + 7
Add, remember, adding a negative number and a positive number is the same as subtracting the negative number from the positive number,
24 = 4
This statement is not true.
Answer:
<h3>FALSE</h3>
Step-by-step explanation:
Given the polynomial f(x) divided by x-4
To check whether the remainder will be equal to f(-4), we need to get whether the value of x is -4 if we set x-4 to zero as shown;
x- 4 = 0
Add 4 to both sides
x - 4 + 4 = 0+4
x = 4
<em>Since the value of x is 4 not -4 hence the remainder will NOT be equal to f(-4). The answer is false</em>
Answer: A ; 120in3 sowwy if im wrong
Step-by-step explanation:
Formula= L times W times H
4 times 6 times 5
6 times 5 = 30
30 times 4 = 120
120 is the answer